2020
DOI: 10.1021/acs.est.0c00792
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Extraction of AFFF-Associated PFASs from Source Zone Soils

Abstract: Poly-and perfluoroalkyl substances (PFASs) derived from aqueous film-forming foam (AFFF) are increasingly recognized as groundwater contaminants, though the composition and distribution of AFFF-derived PFASs associated with soils and subsurface sediments remain largely unknown. This is particularly true for zwitterionic and cationic PFASs, which may be incompletely extracted from subsurface solids by analytical methods developed for anionic PFASs. Therefore, a method involving sequential basic and acidic metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
215
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(228 citation statements)
references
References 41 publications
(104 reference statements)
8
215
1
Order By: Relevance
“…The PFASs were extracted from soil using a triple methanol rinse, and sonication or other extraction methods may have been more appropriate. 77 While this challenges the precise interpretation of the mass balance, a comparison on an order of magnitude basis showing 10 5 ng total PFAS associated with the pre- and postleached soil versus 10 2 –10 3 ng total PFAS observed in the composite leachates strongly suggests that chemical stabilization decreases PFAS leachability into groundwater as well as extractability with methanol rinse. The calculated percentage of PFHxS, PFOS, PFHxA, and PFOA leachability demonstrates that in comparison to the soil-only control from the batch testing, stabilizers reduced the leachability of these PFAAs ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PFASs were extracted from soil using a triple methanol rinse, and sonication or other extraction methods may have been more appropriate. 77 While this challenges the precise interpretation of the mass balance, a comparison on an order of magnitude basis showing 10 5 ng total PFAS associated with the pre- and postleached soil versus 10 2 –10 3 ng total PFAS observed in the composite leachates strongly suggests that chemical stabilization decreases PFAS leachability into groundwater as well as extractability with methanol rinse. The calculated percentage of PFHxS, PFOS, PFHxA, and PFOA leachability demonstrates that in comparison to the soil-only control from the batch testing, stabilizers reduced the leachability of these PFAAs ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We recognize that foc in the first meter below the land surface may be much greater than the foc employed in the present study. Additionally, more complex sorption processes such as electrostatic interactions may lead to enhanced solid-phase adsorption in particular for cationic and zwitterionic PFAS (Barzen-Hanson et al, 2017;Mejia-Avendaño et al, 2020;Nickerson et al, 2020;Xiao et al, 2019). Under these conditions, our simulations would overestimate PFAS leaching.…”
Section: Discussionmentioning
confidence: 99%
“…Polyfluoroalkyl compounds containing one or multiple ionizable groups that were detected at relatively high concentration included AmPr-FHxSA (zwitterion, 17-4111 ng/g), TAmPr-FHxSA (zwitterion, 109-3098 ng/g), FHxSA (anion, 91-545 ng/g), FOSA (anion, 81-366 ng/g), TAmPr-FOSA (zwitterion, 17-206 ng/ g), and AmPr-FOSA (zwitterion, 1.2-145 ng/g). Their detection was expected, as studies have recently reported such nonanionic PFAS to make up a large fraction of fluorosurfactants in AFFF formulations (Adamson et al, 2020;Nickerson et al, 2020). The charge status of these compounds also varies widely, determined by one or multiple ionizable groups, as well as the permanently charged quaternary ammonium group (see Scheme 1).…”
Section: Pfas Detected In Impacted Soilsmentioning
confidence: 98%
“…In many instances, PFAS are directly discharged into soils with little or no treatment, and thereby leaching from soils contributes to the PFAS load in groundwater and surface water. The elevated levels of PFAS are widely observed in the soil, water, sediment, and wildlife samples geographically relevant to the impacted sites, even when the discharges of AFFFs are discontinued for years (Barzen‐Hanson et al, 2017; Nickerson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation